PENGARUH SELF-EFFICACY, OUTCOME EXPECTATIONS, DAN CAREER INTERESTS TERHADAP KESIAPAN KERJA PADA MAHASISWA PROGRAM STUDI PENDIDIKAN ADMINISTRASI PERKANTORAN - Karisma Dewi; Ahmad Saeroji (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the effect of self-efficacy, outcome expectations, and career interests on the work readiness of students in the Office Administration Education Study Program. This research employed a quantitative approach with a causal design. The population consisted of 123 students from the 2023 cohort, with a minimum sample of 94 respondents determined using the Slovin formula and proportionate stratified random sampling technique. Data were collected from 107 respondents through a Likert-scale questionnaire. Data analysis was conducted using multiple linear regression with IBM SPSS Statistics version 26. The results showed that self-efficacy, outcome expectations, and career interests had a positive and significant effect on students’ work readiness, both partially and simultaneously. Among the three variables, outcome expectations emerged as the most dominant factor influencing students’ work readiness. These findings indicate that expectations regarding career outcomes play an important role in encouraging students to better prepare for entering the workforce. The novelty of this study lies in examining the three variables in an integrated model within the context of Office Administration Education students, which has been relatively limited in previous studies. This study contributes to the development of work readiness research and provides a basis for designing learning strategies and career guidance programs in higher education.